Bundling of STDs and HIV in Prevention Messages. Issue 1 (5th January 2015) - Poehlman, Jon; Uhrig, Jennifer D; Friedman, Allison; Scales, Monica; Forsythe, Ann; Robinson, Susan J
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to explore peoples cognitive perceptions of HIV and other sexually transmitted diseases (STDs) to inform decisions on message development with regard to message bundling, with limited research on the concept of bundling-related prevention messages and no studies that consider the bundling of HIV and other STD prevention messages. Design/methodology/approach – Individual and small-group interviews were conducted with 158 African American men and women to explore perceptions of STDs and communication preferences. Open-ended questions and a pile-sort exercise were used to elicit individuals' judgments on similarities of 12 STDs, including HIV. Interview data were coded and analyzed for themes and patterns; pile sort data were analyzed using multidimensional scaling (MDS) and cluster analysis to visualize the set of relations identified from the piles. Findings – STDs and HIV are associated with stigma, risk behaviors and personal responsibility. The card sorting activity revealed two primary dimensions by which people organized STDs: seriousness and curability. Potential clusters of STDs that correspond to participants described sorting strategies were identified and they may have implications for message bundling. Disaggregation of the data by sex and age revealed slight variations in the relationships of HIV and human papillomavirus (HPV) to other STDs. Originality/value – By identifying a set of cognitive attributes people use in organizing the overall semantic domain of STDs, ideas can be generated for how best to combine STD and HIV messages to meet public health communication goals.